Engineering cellular bridges to collectively regulate cell migration and morphology - Hu, Benhui (2015)
In living systems, cells rely on cell signaling to explore and respond to stimulus from their surroundings. The process promotes the individual cells to realize proper functioning, and more importantly, this process facilitates the communication among cells and groups of cells. Collectively, cellular communication contributes significantly for regeneration and developmental biology. Based on the essential role of cellular bridge in cellular communication, we systematically investigated the cellular bridges at varied scales and their functions in regulate cell migration and morphology. Firstly, via regulating the subcellular bridges formed on extracellular matrix (ECM) with discrete adhesions sites and variable rigidity, the multicellular morphology and its related protective function determined by the efficiency of cells in maintaining its continuity and integrity can be switched on or off by modifying their environment. Then, by forming cellular bridge between muscle cell pair and utilizing the high tension within the bridge, we revealed an unanticipated mode of oscillation induced cell migration, providing an effective way to inhibit contact inhibition locomotion (CIL), which may help minify intimal thickening during in-stent restenosis and prevent vein graft failure. Lastly, through increasing the cellular bridge to multicellular scale, we investigated the formation and regulation of multicellular bridges over large non-adhesive regions. The studies on the geometry of ECM and orientation of cell migration provide in-depth understanding of the biophysical mechanism for cellular bridge formation and the corresponding healing efficiency. The elucidated interplay between the geometrical aspects of ECM and the multicellular bridges would allow us to optimize the migratory strategies for wound healing. As cell migration and morphology are critical for regeneration and developmental biology. Our findings provide unanticipated modes to engineer artificial, bio-compatible scaffolds, which are then potentially applied for developmental and regenerative biology.